Performance assessment and economic and ecological analysis of carbon-negative recycled crumb rubber-based geopolymers - Sarkaz, Abdussalam M. Hasan; Danish, Aamar; Memiş, Selçuk; Yaprak, Hasbi; Gencel, Osman; Ozbakkaloglu, Togay (Elsevier BV, 2024)
Geopolymer technology offers several compelling ecological and economic advantages regarding waste management. This research investigates the effect of size (less than equal to 4 mm) and amount (5-15 vol%) of crumb rubber (CR) as fine aggregate on the physical, mechanical, and durability properties of geopolymers. The economic and ecological analyses were also performed to determine the effect of producing CR-based geopolymers on cost and the environment. The results revealed that the addition of CR negatively influences the physical, mechanical, and durability properties; nonetheless, incorporation of 5-10 vol% CR with a size less than 2 mm exhibited satisfactory performance fit for medium-strength structures such as foundations, partition walls, sidewalks, drainage structures, etc. Additionally, although the incorporation of CR slightly increases the pro-duction cost (3.99-11.97%) and embodied energy (0.08-0.24%) of resulting geopolymers, the embodied CO2 emission of 5, 10, and 15 vol% CR-incorporated geopolymer mixes is 90.4,-143.6 and-377.6 kgCO2e/m3, respectively. In contrast, the embodied CO2 emissions of conventional geopolymer mix is 324.4 kgCO2e/m3, which shows the negative carbon emission potential of CR-modified geopolymers, providing a glimmer of hope for sustainable development in the construction industry.
Keywords: Fine Aggregate; Sustainable Development; Geopolymer; Crumb Rubber; Negative Carbon Emissions